Psychological pushing propagation in crowds—Does the observation of pushing behavior promote further intentional pushing? - Lügering, Helena; Alia, Ahmed; Sieben, Anna (Frontiers in Social Psychology, 2023)
When large numbers of people come together (e.g., at concerts or religious gatherings), critical situations can arise easily. While physical factors such as crowd density play a role, people's behavior can also affect crowd dynamics. For example, pushing and shoving, which are closely related to density, can quickly contribute to potentially dangerous dynamics. There is little extant research, however, on why people start pushing in the first place. Aside from individual reasons (e.g., motivation), social reasons might also play a role: an initial instance of pushing might be imitated or spark a competition if the pusher seems to reach the goal faster or the behavior of individuals defines a group norm whether pushing is allowed or not. Practically speaking, these social factors should lead people to push because they perceive other pushers, or, in other words, a psychological pushing propagation occurs. To address this question, the behavior (pushing or non-pushing) of people in 14 different experimental runs of crowds walking through a bottleneck (N = 776) was assessed by two independent raters with the help of a rating system of forward motion. This assessment was then linked to the spatiotemporal positions of the participants to combine it with the neighborhood relations. Based on that, it was analyzed whether individuals who started to push were more likely to be in the direct neighborhood of individuals who were already pushing. Results showed a small but significant effect suggesting that there is an influence, but that pushing is not overly "contagious".